Green Waves: How Leaders’ Actions Shape Employee Behaviours, a Moderated Mediation Model of Organizational Green Culture and Personality Traits - Zheng, Cheng; McKay, Ruth; Ciocirlan, Cristina (International Journal of Applied Research in Management and Economics, 2024)
In the recent decade, the literature on corporate greening, sustainability, and environmental performance has burgeoned. Organizational citizenship behaviour for the environment (OCBE), defined as employees’ voluntary behaviours that aim to contribute to the organization’s environmental management, has recently attracted considerable scholarly attention. Through a holistic review and synthesis of the current literature on OCBE, we aim to bridge the gaps in the literature and provide new and novel insights into the cascading effect of leaders’ OCBE throughout the organization. Specifically, we delineate the link between leaders’ OCBE engagement and followers’ propensity to engage in OCBE, a link mediated by organizational green culture (OGC). In addition, given the lack of attention to intra-personal variables in the OCBE literature, we also aim to explain the moderating effect of personality in the proposed mediated relationship. Theoretically, from the social learning and social exchange lenses, the paper contributes to the current literature by explaining the interplay between interpersonal (leaders’ behaviour) and organizational (OGC) variables in predicting employees’ OCBE. We also highlight the role of the personality trait of openness to experience as a boundary condition that can affect employees’ propensity to perform high-intensity OCBE. From a practical perspective, this paper offers valuable insights for management and HR practitioners who are committed to effective environmental management and sustainability.